Integrated quality and sustainability assessment in construction: a conceptual model - Srdić, Aleksander; Šelih, Jana (Technological and Economic Development of Economy, 2011)
In today’s world, the definition of quality has been extended to more comprehensive level, which also comprises sustainable performance. The paper systematically builds an integrated model that includes quality as well as sustainable performance of the built environment and accompanying construction processes. This model for the “Integrated Quality and Sustainability Performance Assessment in Construction” presents a three-level arrangement, namely: the structure, process/ project, and construction product. We propose a holistic sustainability assessment methodology based on the authors’ previous research work for structures. The strict implementation of quality and environmental management systems in the participating organisations and in the whole construction project guarantees quality and environmental performance at project/process level. On the construction product level, we complement the existing requirement of providing a statement of conformity for each product of the structure with the Environmental Product Declaration (EPD) for all construction products. We use the Life Cycle Assessment (LCA) methodology to obtain the EPDs for specific construction products; in this way, we can evaluate their environmental impacts throughout the life cycle of a product or structure. On the structure level, a model for the integrated sustainability and quality assessment, which was previously proposed by the authors, is employed. Integration of all three levels ensures that the desired plateau of quality and sustainability performance is achieved for structures, processes and products. In the present version, the model is tailored to the specific features of buildings, and the sustainability aspect is limited to the environmental performance. An investigation of measures required to implement the proposed model into practice shows that clients have a major influence upon the procurement rules. Consequently, the targeted audience of potential users is that of clients procuring buildings. First published online 18 Jan 2012